Taxing childcare: effects on family labor supply and children - Gathmann, Christina; Saß, Björn (SOEP papers on multidisciplinary panel data research, 2012)
Previous studies report a wide range of estimates for how female labor supply responds to childcare prices. We shed new light on this question using a reform that raised the prices of public daycare. Parents respond by reducing public daycare and increasing childcare at home. Parents also reduce informal childcare indicating that public daycare and informal childcare are complements. Female labor force participation declines and the response ist strongest for single parents and low-income households. The short-run effects on cognitive and non-cognitive skills are mixed, but negative for girls. Spillover effects on older siblings suggest that the policy affects the whole household, not just targeted family members. -- Childcare ; Labor supply ; Cognitive skills ; Family Policy ; Germany